2014
DOI: 10.1007/s10571-014-0064-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Oxaloacetate in a Focal Brain Ischemic Model in the Rat

Abstract: During an ischemic event, the well-regulated glutamate (Glu) homeostasis is disturbed, which gives rise to extremely high levels of this excitatory neurotransmitter in the brain tissues. It was earlier reported that the administration of oxaloacetate (OxAc) as a Glu scavenger reduces the Glu level in the brain by enhancing the brain-to-blood Glu efflux. Here, we studied the neuroprotective effect of OxAc administration in a new focal ischemic model in rats. Occlusion of the middle cerebral artery resulted in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
(32 reference statements)
2
10
1
Order By: Relevance
“…The ischemic-like cell death is also called oncosis and has been shown to be involved in diseases such as ischemic heart disease and stroke [ 37 – 39 ]. Consistent with our results, other studies have shown that OAA is neuroprotective against ischemic stroke and that a combination of human rGOT1 with low doses of OAA induces a protective effect after cerebral ischemia [ 40 , 41 ]. Moreover, evidence also indicates that NAD + is able to protect cells against ischemic injury [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…The ischemic-like cell death is also called oncosis and has been shown to be involved in diseases such as ischemic heart disease and stroke [ 37 – 39 ]. Consistent with our results, other studies have shown that OAA is neuroprotective against ischemic stroke and that a combination of human rGOT1 with low doses of OAA induces a protective effect after cerebral ischemia [ 40 , 41 ]. Moreover, evidence also indicates that NAD + is able to protect cells against ischemic injury [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…14,15,17,31 This novel mechanism has also been validated for other independent laboratories with similar results. 16,32,33 However, despite the beneficial effect observed in ischemic stroke models and other neurologic disorder animal models, in this study, administration of two of the most efficient blood glutamate grabbers used (oxaloacetate or rGOT1) was not able to reduce hematoma lesion or improve the neurologic outcome in animals subjected to an ICH. Reduction of blood glutamate levels showed that both drugs had indeed an effect on lowering blood and subsequently brain glutamate levels.…”
Section: Discussioncontrasting
confidence: 66%
“…To confirm that the neuroprotective effect was due to a decrease in brain glutamate levels, spectroscopic analysis revealed that the increase in brain glutamate observed in control animals after MCAO was clearly reduced in animals treated with OxAc. These results were also validated by other independent laboratories 15 .…”
Section: Blood To Brain Glutamate Grabbingsupporting
confidence: 75%